Short-term interaction between silent and devastating earthquakes in Mexico - V. M. Cruz-Atienza (Nature Portfolio, 2021)
This study shows how seismic and aseismic events are related in Mexico between 2017 and 2019. Based on a series of observations and models, the study suggests that the Mw 8.2 intraslab earthquake of 8 September 2017 severely altered the mechanical properties of the plate interface, facilitating the interaction between the events and disrupting the slow slip cycles at a regional scale.